Differential Pulse Voltammetric Determination of Serotonin Using an Acid-Activated Multiwalled Carbon Nanotube - Over-Oxidized Poly(3,4-ethylenedioxythiophene) Modified Pencil Graphite Electrode - Gorduk, Ozge (TAYLOR & FRANCIS INC, 2020)
In this study, acid-activated multi-walled carbon nanotubes (AA-MWCNT) and poly(3,4-ethylenedioxythiophene) (PEDOT) were deposited on a pencil graphite electrode (PGE) surface for electrochemical sensing applications. The acid-activated multi-walled carbon nanotube/over-oxidized poly(3,4-ethylenedioxythiophene) modified pencil graphite electrode (AA-MWCNT/OO-PEDOT/PGE) was characterized using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). The sensing properties of the obtained surface were examined for the voltammetric determination of serotonin in a phosphate buffer solution. The effects of the pH, adsorption time, over-oxidation and polymerization parameters on the electrochemical properties of serotonin were investigated. The effects of possible interfering substances were evaluated. The detection limit was determined to be 0.092 mu M based on a signal-to-noise ratio of 3. Analytical applications of AA-MWCNT/OO-PEDOT/PGE were successfully tested for the determination of serotonin in human blood serum samples.
Keywords: Differential pulse voltammetry (DPV); electrochemical sensor; human blood serum; multi-walled carbon nanotube; pencil graphite electrode (PGE); poly(3; 4-ethylenedioxythiophene); serotonin; PERFORMANCE LIQUID-CHROMATOGRAPHY; ELECTROCHEMICAL OXIDATION; SENSITIVE DETERMINATION; URIC-ACID; ONE-STEP; DOPAMINE; SENSOR; 5-HT; FILM; NEUROTRANSMITTERS; Chemistry